PENINGKATAN HASIL BELAJAR MATERI COULD I HAVE ONE MELALUI MEDIA GAMBAR SISWA KELAS VIIG SMPN 2 BUNGO - emi saswita (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
learning english is one of the subject that students dont like to study and also which difficult materials, its happen because this language is a foreign language whose spelling and pronunciation are different from Indonesian. This is indicated by the results of student evaluations or tests which are on average below the KKM set by the school, namely 76.00, Therefore, it is necessary Methods and media that make students interested. One thing that is applied is using image media. The aim of this research is to improve the learning outcomes of the material Can I Have One through the image media of Class VII G students of SMPN 2 BUNGO. The method used in this research is action research which consists of 2 (two) cycles, and each cycle consists of: planning, implementation, observation and reflection. This research uses a classroom action research design which consists of pre-cycles, cycles. I, and cycle II. Each cycle consists of stages (1) planning, (2) action, (3) observation, and (4) reflection. The subject of this research is the personality skills of class VII G students, while the data source is class VII G students of SMP Negeri 2 Bungo. Based on the results of action research, Image Media can improve the learning outcomes of Could I Have One material for Class VIIb students at SMPN 2 Bungo. With the results, namely cycle I (25%), cycle II (90%)